l-Thyroxine in an Oral Liquid or Softgel Formulation Ensures More Normal Serum Levels of Free T4 in Patients with Central Hypothyroidism - Benvenga, Salvatore; Capodicasa, Giovanni; Perelli, Sarah (Frontiers in Endocrinology, 2017)
Context: L-thyroxine therapy of central hypothyroidism (CH) is guided by measurements of serum free thyroxine (FT4), which should be above the midnormal range value (MNRV). In some countries, novel formulations of oral L-thyroxine (liquid or softgel) are available further to the classic tablets. The intestinal absorption of either novel formulation is greater than tablets in patients with primary hypothyroidism. Objective: To evaluate if new oral formulations of L-T4 could be considered optimal in patients with central hypothyroidism who do not reach the FT4 target using tablet L-thyroxine. [Q5 Rev1] Design: Our observation of six patients with isolated CH and serum FT4 below MNRV under stable adequate doses of tablet L-thyroxine (median 1.51 µg/Kg bw/day), prompted us to switch them to liquid (n= 4) or softgel (n=3) L-thyroxine at the same dose, and verify whether FT4 increased above MNRV. A seventh patient with FT4 above MNRV was enrolled because she wanted a “more modern formulation”. Post-switch FT4 was measured at least twice with the same kit as pre-switch FT4. Results: In the first six patients, post-switch FT4 averaged 13.0±1.6 pg/ml compared to 10.4±1.8 pre-switch FT4 (P= 0.00026), with 11/13 (85%) measurements above MNRV compared to 0/20. In the liquid or softgel L-thyroxine group, post-switch FT4 averaged 13.1±1.6 vs 10.6±0.9 pg/ml pre-switch (P=0.0004) or 12.9±2.1 vs 10.3±2.4 (P=0.048) respectively. [Q5 Rev1] In the seventh patient (switched to liquid L-thyroxine), averages were 18.3 vs 15.2 pg/ml, and proportions 4/4 vs 2/2. Conclusion: In CH patients oral liquid or softgel L-thyroxine administered at the same doses as tablet L-thyroxine ensures target serum FT4 levels above MNRV that tablet L-thyroxine may miss. In turn, this performance confirms suggests [Q5 Rev2] the more favorable pharmacokinetics profile of either novel formulation compared with the tablet formulation.